Improving phosphorus efficiency in cereal crops: Is breeding for reduced grain phosphorus concentration part of the solution? - Rose, Terry; Liu, Lei; Wissuwa, Matthias (Frontiers in Plant Science, 2013)
Given the non-renewable nature of global phosphate reserves, there is a push to increase the phosphorus (P) efficiency of agricultural crops. Research has typically focussed on investigating P acquisition efficiency or internal P utilization efficiency to reduce crop fertilizer requirements. A novel option that would reduce the amount of P exported from fields at harvest, and may ultimately reduce P fertilizer requirements, would be to reduce the amount of P translocated to grains to minimize grain P concentrations. While such a trait has been mentioned in a number of studies over the years, there has not been a concerted effort to target this trait in breeding programs. In this perspective piece we explore the reasons why a low grain P trait has not been pursued, and discuss the potential benefits and drawbacks of such a trait in the context of breeding to improve the P efficiency of cropping systems.